2001
DOI: 10.1007/s001250100656
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil citrate for the treatment of erectile dysfunction in men with Type II diabetes mellitus

Abstract: Diabetes mellitus is very common, with Type II (noninsulin-dependent) diabetes mellitus accounting for 90 % to 95 % of the diagnosed patients [1]. A frequent complication of diabetes is erectile dysfunction (ED), with an estimated prevalence of 20 % to 85 % (ranging from mild to complete ED) [2], which occurs at an earlier age than in non-diabetic men. In the Massachusetts Male Aging study [3], men with treated diabetes had an age-adjusted prevalence of complete ED (no erections) of 28 %, which was approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 17 publications
9
85
0
1
Order By: Relevance
“…11 The most recently reported study involving patients with type 2 diabetes reports a 64.6% response rate to sildenafil compared with a 10.5% response rate in diabetic patients receiving placebo. 13 Sildenafil was effective in improving ED in these studies, even in cases of poor glycemic control; the response rate, however, for patients with multiple chronic complications was lower, reflecting the severity of the disease. A retrospective analysis of combined data from 11 double-blind, placebo-controlled trials of sildenafil (which included 152 and 822 patients with type 1 and 2 diabetes, respectively, and 1693 patients without diabetes) confirmed that although treatment response was lower for patients with diabetes compared with those without diabetes, the efficacy of sildenafil was similar for men with type 1 and type 2 diabetes, with more than three times as many men receiving sildenafil reporting significant improvement in erectile function compared with those receiving placebo.…”
Section: Efficacy In Clinical Trialsmentioning
confidence: 67%
“…11 The most recently reported study involving patients with type 2 diabetes reports a 64.6% response rate to sildenafil compared with a 10.5% response rate in diabetic patients receiving placebo. 13 Sildenafil was effective in improving ED in these studies, even in cases of poor glycemic control; the response rate, however, for patients with multiple chronic complications was lower, reflecting the severity of the disease. A retrospective analysis of combined data from 11 double-blind, placebo-controlled trials of sildenafil (which included 152 and 822 patients with type 1 and 2 diabetes, respectively, and 1693 patients without diabetes) confirmed that although treatment response was lower for patients with diabetes compared with those without diabetes, the efficacy of sildenafil was similar for men with type 1 and type 2 diabetes, with more than three times as many men receiving sildenafil reporting significant improvement in erectile function compared with those receiving placebo.…”
Section: Efficacy In Clinical Trialsmentioning
confidence: 67%
“…15,35,36 However, sildenafil does not have the same efficacy in improving erectile function as measured by the International Index of Erectile Function in diabetic patients when compared to other ED etiologies. 16 Sildenafil requires at least partial function of NANC penile nerves to be effective, and, therefore, men who have DM or have undergone non-nerve-sparing radical prostatectomy are less likely to respond.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil has been well characterized in diabetic patients, with success rates of 56-67% in this population, compared with 10-29% with placebo. [16][17][18] For most patients the doses are 25, 50 or 100 mg 1 h before intercourse, and can be taken only once daily. Sildenafil has no effect in the absence of sexual stimulation, and is contraindicated in patients who are taking nitrates for cardiovascular disease.…”
Section: Diagnostic/therapeutic Proposalmentioning
confidence: 99%